Iridescence and spectral filtering of the gyroid-type photonic crystals in Parides sesostris wing scales - Wilts, Bodo D. (The Royal Society, 2012)
The cover scales on the wing of the Emerald-patched Cattleheart butterfly, Parides sesostris, contain gyroid-type biological photonic crystals that brightly reflect green light. A pigment, which absorbs maximally at approximately 395 nm, is immersed predominantly throughout the elaborate upper lamina. This pigment acts as a long-pass filter shaping the reflectance spectrum of the underlying photonic crystals. The additional effect of the filtering is that the spatial distribution of the scale reflectance is approximately angle-independent, leading to a stable wing pattern contrast. The spectral tuning of the original reflectance is verified by photonic band structure modelling.